Nilai Perusahaan dan Faktor-Faktor yang Mempengaruhinya: Analisis Likuiditas, Profitabilitas, Solvabilitas, dan Ukuran Perusahaan - Dassaad; Zulhida Tiara Bumi; Riyanti; Dyah Palupi (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to find out and analyze the influence of Liquidity, Profitability, Solvency, Company Size on Company Value in Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the period of 2019-2023. The data in this study is secondary data in the form of annual reports obtained from the official website of the IDX and each company. The independent variables in this study are Liquidity, Profitability, Solvency, and Company Size. The dependent variable is the Company Value. The theory in this study uses is signalling theory. The method in this study uses a quantitative method. The data analysis technique uses multiple linear regression where previously the data has been tested using descriptive statistical tests, classical assumption tests and using different tests. The results of this study show that partially Liquidity negative affect and Profitability positive affect the value of the company. Meanwhile, Solvency and Company Size have no effect on the company's value.